2014
DOI: 10.1093/aje/kwt308
|View full text |Cite
|
Sign up to set email alerts
|

No Rise in Incidence but Geographical Heterogeneity in the Occurrence of Primary Biliary Cirrhosis in North East England

Abstract: In this study, we examined temporal changes in the incidence of primary biliary cirrhosis (PBC) and investigated associations between PBC incidence and sociodemographic factors and spatial clustering. We included 982 patients aged ≥40 years from North East England with incident PBC diagnosed during 1987–2003. Age-standardized incidence rates with 95% confidence intervals were calculated. Negative binomial regression was used to analyze incidence and socioeconomic deprivation. Clustering analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 34 publications
6
34
1
Order By: Relevance
“…It is very important to note that the lack of temporal clustering seen here does not contradict our earlier analyses (McNally et al, 2009(McNally et al, , 2011(McNally et al, , 2014. The finding of spatial clustering indicates the involvement of a localised environmental factor (McNally et al, 2014), whilst the space-time clustering is consistent with the involvement of an aetiological agent that has an irregular occurrence in time and space, taking into account general excesses in certain geographical areas or temporal periods (McNally et al, 2009). Also, the finding of seasonal variation is consistent with the involvement of a regularly occurring seasonal exposure in aetiology (McNally et al, 2011).…”
Section: Notessupporting
confidence: 66%
See 2 more Smart Citations
“…It is very important to note that the lack of temporal clustering seen here does not contradict our earlier analyses (McNally et al, 2009(McNally et al, , 2011(McNally et al, , 2014. The finding of spatial clustering indicates the involvement of a localised environmental factor (McNally et al, 2014), whilst the space-time clustering is consistent with the involvement of an aetiological agent that has an irregular occurrence in time and space, taking into account general excesses in certain geographical areas or temporal periods (McNally et al, 2009). Also, the finding of seasonal variation is consistent with the involvement of a regularly occurring seasonal exposure in aetiology (McNally et al, 2011).…”
Section: Notessupporting
confidence: 66%
“…Table 3 summarises key findings from studies in northeast England of spatial, spatio-temporal and temporal clustering of PBC, as well as of seasonal variation, following the approach taken in an earlier assessment of clustering of childhood cancer (McNally and Eden, 2004). It is very important to note that the lack of temporal clustering seen here does not contradict our earlier analyses (McNally et al, 2009(McNally et al, , 2011(McNally et al, , 2014. The finding of spatial clustering indicates the involvement of a localised environmental factor (McNally et al, 2014), whilst the space-time clustering is consistent with the involvement of an aetiological agent that has an irregular occurrence in time and space, taking into account general excesses in certain geographical areas or temporal periods (McNally et al, 2009).…”
Section: Notessupporting
confidence: 54%
See 1 more Smart Citation
“…Clusters of PBC patients in a specific area at a specific time can identify candidate risk factors for PBC development, and such candidate risk factors can then be studied more specifically in case-control studies. In their study, McNally et al [37] found clustering of PBC cases in and around Newcastle in North East England, with a higher PBC incidence in socioeconomically deprived areas. They concluded that the clustering is consistent with hypotheses that infectious agents, toxins, or lifestyle factors precipitate PBC.…”
Section: Aihmentioning
confidence: 86%
“…Since then, studies from North East England have found even higher incidence rates: Metcalf et al [35] found an incidence rate of 4.30 per 100,000 in the city of Newcastle in 1987-1994 [35] , and this was followed by a study by James et al [36] who studied a wider area around the city of Newcastle and found an incidence rate of 3.22 per 100,000 in 1994, rising from 2.30 in 1987. This rise in incidence around Newcastle was later attributed to better case-finding, when McNally et al [37] studied the same area and found no increase in PBC incidence between 1987 and 2003 [37] , but PBC incidence is in fact higher in the city of Newcastle than in its more sparsely populated surroundings [50] . This finding indicates that the prevalence of risk factors for PBC is higher in Newcastle.…”
Section: Aihmentioning
confidence: 98%